Analysis of electrocution accidents in complex systems based on four ‎models: HFACS, FTA, AcciMap, and STAMP ‎ - Alasmari, Mobasher; Balkhyour‎, Mansour; Chakroun‎, Radhouane (Journal of King Abdulaziz University-Meteorology Environment and Arid Land Agriculture Sciences, 2025)
This study aims to the examination of four accident causation models namely: human factors and classification system (HFACS), Fault tree analysis (FTA), AcciMAp, and the Systems-Theoretic Accident Model and Processes (STAMP) to study the causation of electrocution accidents and the advantages and drawbacks inherent in every model. Two objectives of the study are: to determine the most appropriate methods for investigating electrocution accidents within complex systems and to comprehend the features of four methodologies concerning their conceptualization of accident causation. Methodology: to investigate the causation of electrocution accidents, the study involves a systematic approach that includes a literature review, gathering relevant data, analyzing various factors such as electrical systems, equipment, human behavior, and environmental conditions, identifying hazards and risk factors, and determining the sequence of events leading to the accident. Conclusion: HFACS and AcciMap are found to be more effective as they both consider the failures and defects at different levels of organization. It is found that establishing clear communication channels among all levels of the organization is a critical aspect of implementing a holistic approach to safety management.